TRANSITIVE CONSTRUCTIONS OF A COMPLEX SENTENCE WITH SYNCHRETIC RELATIONS “CONDITION-RESULT” - Шундель, Татьяна (SWorldJournal, 2020)
The paper considers the questions of differentiation of transitive structures of complex sentences with syncretic nature and determines the fact that one of the key aspects of unresolved problems in the syntax of complex English sentences is a transitive